PENGARUH KEAKTIFAN BERORGANISASI DAN PERILAKU BELAJAR TERHADAP PRESTASI AKADEMIK MAHASISWA PENDIDIKAN MATEMATIKA UIN ALAUDDIN MAKASSAR - Nur Fitriani Safar; Muhammad Rusydi Rasyid; Nur Yuliany (Al Asma: Journal of Islamic Education, 2019)
This research is an Ex-Post Facto research that aims to determine the effect of organizational activeness and learning behavior on academic achievement of students of mathematics education at UIN Alauddin Makasssar. Data analysis techniques used descriptive statistical analysis of percentages and multiple linear regresy analysis. Descriptive analysis result showed that the percentage of student activiness in the category of good with a percentage of 56%, learning behavior included in the good category with a percentage of 68%, and academic achivment included in the category of very satisfying with the interval values of 3.01 – 3.50. The result of multiple linear regression analysis showed that the activeness of organization and learning behavior together significantly influenced the academic achievement of students of mathematics education at Alauddin UIN Makassar, with a regression equation Ŷ = 3.551 - 0.014X1 + 0.012X2 with a coefficient of determination r2 = 0.332. from the results of above study, it can be concluded that there is an effect of organizational activeness and learning behavior on academic achievement of mathematics education students at UIN Alauddin Makassar. AbstrakPenelitian ini merupakan penelitian Ex-Post Facto yang bertujuan untuk mengetahui pengaruh keaktifan berorganisasi dan perilaku belajar terhadap prestasi akademik mahasiswa pendidikan matematika UIN Alauddin Makassar. Teknik analisis data menggunakan analisis statistik deskriptif presentase dan analisis regresi linier berganda. Hasil analisis deskriptif persentase menunjukan bahwa keaktifan berorganisasi mahasiswa masuk dalam kategori baik dengan persentase 56%, perilaku belajar termasuk dalam kategori baik dengan persentase 68%, dan prestasi akademik termasuk dalam kategori sangat memuaskan dengan interval nilai 3,01 – 3,50. Hasil analisis regresi linier berganda menunjukkan bahwa keaktifan berorganisasi dan perilaku belajar secara bersama-sama berpengaruh secara signifikan terhadap prestasi akademik mahasiswa pendidikan matematika UIN Alauddin Makassar, dengan persamaan regresi Ŷ=3.551 - 0,014X1 + 0,012X2 dengan koefisien determinasi r2 = 0,332. Dari hasil penelitian di atas, maka dapat disimpulkan bahwa terdapat pengaruh keaktifan berorganisasi dan perilaku belajar terhadap prestasi akademik mahasiswa pendidikan matematika UIN Alauddin Makassar.